Light grazing reduces temporal variation in soil organic carbon in an alpine peatland: Perspectives from fungal communities - Li, Yang; Liu, Jianliang; Chen, Huai; Huang, Xinya; Tang, Li (Agriculture, ecosystems & environment, 2025)
Waterlogged alpine peatlands harbour substantial reserves of recalcitrant soil organic carbon (SOC) that is mainly decomposed by soil fungi. Even a slight fluctuation in peatland SOC can considerably alter C emissions, thereby impacting the future trajectory of climate change. These peatlands are often subject to yak grazing, which can affect ecosystem functions. However, how grazing regulates microbially mediated temporal variations in SOC in alpine peatlands remains largely unclear. Therefore, we conducted a field experiment on the Zoige Plateau to explore the effects of grazing on peatland soil C content and its association with soil fungal communities during different seasons (spring, summer, and autumn). Grazing significantly increased SOC in spring but not in the subsequent seasons. Furthermore, grazing significantly increased soil water contents in summer, dissolved organic carbon contents in autumn, and N-acetyl-β-D-glucosaminidase and leucine aminopeptidase activities in spring and autumn, but decreased phenol oxidase activity in spring and summer. Grazing significantly reduced fungal diversity at α and β scales. The coefficient of variation of SOC was significantly reduced by grazing, whereas similar trends were not observed for dissolved organic carbon or for dissolved organic and inorganic nitrogen. In the fenced area, the coefficient of variation of fungal species richness was the most important factor for predicting that of SOC. In the grazed area, coefficient of variation of soil NH4+-N contributed the most to that of SOC. These findings underscore the pivotal role of fungal community in affecting SOC dynamics in alpine peatlands, which is crucial for understanding the ecological processes that maintain soil C cycling in alpine ecosystems. •Grazing significantly increased SOC in spring, but not the subsequent seasons.•Fungal α and β diversity underwent significant reductions due to grazing.•Fungal α diversity was the most critical factor driving SOC variations in fenced area compared to grazed area.•Our results showed a key role of fungal community in driving SOC dynamics in alpine peatlands.